Cysteine proteinase C1A paralog profiles correspond with phylogenetic lineages of pathogenic piroplasmids - Ascencio, Mariano (2018)
Piroplasmid parasites comprising of Babesia, Theileria, and Cytauxzoon are transmitted by ticks to farm and pet animals and have a significant impact on livestock industries and animal health in tropical and subtropical regions worldwide. In addition, diverse Babesia spp. infect humans as opportunistic hosts. Molecular phylogeny has demonstrated at least six piroplasmid lineages exemplified by B. microti, B. duncani, C. felis, T. equi, Theileria sensu stricto (T. annulata, T. parva, and T. orientalis) and Babesia sensu stricto (B. bovis, B. bigemina, and B. ovis). C1A cysteine-proteinases (C1A-Cp) are papain-like enzymes implicated in pathogenic and vital steps of the parasite life cycle such as nutrition and host cell egress. An expansion of C1A-Cp of T. annulata and T. parva with respect to B. bovis and B. ovis was previously described. In the present work, C1A-Cp paralogs were identified in available genomes of species pertaining to each piroplasmid lineage. Phylogenetic analysis revealed eight C1A-Cp groups. The profile of C1A-Cp paralogs across these groups corroborates and defines the existence of six piroplasmid lineages. C. felis, T. equi and Theileria s.s. each showed characteristic expansions into extensive families of C1A-Cp paralogs in two of the eight groups. Underlying gene duplications have occurred as independent unique evolutionary events that allow distinguishing these three piroplasmid lineages. We hypothesize that C1A-Cp paralog families may be associated with the advent of the schizont stage. Differences in the invertebrate tick host specificity and/or mode of transmission in piroplasmid lineages might also be associated with the observed C1A-Cp paralog profiles.